Mixed diboration of alkenes in a metal-free context. Issue 9 (17th December 2014) - Miralles, Nuria; Cid, Jessica; Cuenca, Ana B.; Carbó, Jorge J.; Fernández, Elena
Abstract : Simultaneous addition of two different boryl moieties to alkenes with unequivocal formation of the less reactive C–B bond in the internal position, assisted by OMe − . Abstract : Experimental and theoretical rationalization on regioselective mixed diboration of alkenes, with the unsymmetrical diboron reagent Bpin–Bdan, providing the protecting Bdan moiety in the internal position.